2017
DOI: 10.15761/ams.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of zeolites on plant photosynthesis

Abstract: Besides the effect of zeolites against plant diseases and insect pests, zeolites may also have beneficial effects for the treated plant itself. Zeolites are able to adsorb CO2, which may influence photosynthesis. Zeolites may also reduce leaf temperature by reflecting the infrared radiation. These properties lead to a reduction of transpiration rate, which may improve the water-use efficiency, the yield and the fruit quality. In this study, the possible beneficial effects of zeolites on plant growth, dry weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
2
26
0
1
Order By: Relevance
“…Also, zeolite alone increased the total soluble sugars of canola [89], and when it was combined with Si, it increased the total solids content of onion. In addition, the nanoparticles play an important role in enhancing the leaf photosynthesis rate and CO 2 assimilation, as mentioned before, which increases the accumulation of carbohydrate and protein content in the economic parts [73][74][75]. Salt toxicity leads to oxidative damage and membrane lipid peroxidation [71,105,106].…”
Section: Impacts Of Soil Salinity On Chemical Compositions Of Potato mentioning
confidence: 92%
See 1 more Smart Citation
“…Also, zeolite alone increased the total soluble sugars of canola [89], and when it was combined with Si, it increased the total solids content of onion. In addition, the nanoparticles play an important role in enhancing the leaf photosynthesis rate and CO 2 assimilation, as mentioned before, which increases the accumulation of carbohydrate and protein content in the economic parts [73][74][75]. Salt toxicity leads to oxidative damage and membrane lipid peroxidation [71,105,106].…”
Section: Impacts Of Soil Salinity On Chemical Compositions Of Potato mentioning
confidence: 92%
“…Salinity also has a great detrimental effect on electron transport chain, photophosphorylation, and enzymatic activities of plants [50,71,72]. On the other hand, scientists have reported that supplementary application of Zn, Si, B, and zeolite nanoparticles enhanced the chlorophyll formation and photosynthetic activity of plants [21,[73][74][75]. Silicon supplementation was widely reported to improve photosynthesis parameters under salinity stress conditions.…”
Section: Impacts Of Soil Salinity On Leaf Chlorophyll and Photosynthementioning
confidence: 99%
“…They showed that the use of zeolite had a substantial influence on plant fresh and dry weight, plant height of fodder corn. Due to their extraordinary sponginess, zeolites can absorb water up to 60% of their volume (De Smedt et al 2017), and hence, it can provide water to the root of plants for a longer time. In agreement with our results, Moreno et al (2017) reported that the application of zeolite increased soil chemical fertility at the beginning of barley cultivation and enhanced hydro-soluble concentrations of the nutrients in soil that resulted in enhancement of barley yield.…”
Section: Di1 Di2 Di3mentioning
confidence: 99%
“…Through choosing the correct type of zeolite when adding it as a modifier to the soil, by selective adsorption and controlled release of nutrients from zeolite, it increases the longlasting readiness of water and nutrients and thus helps to improve plant growth (De Smedt et al 2017). As De Smedt et al (2017) investigated, the use of zeolite guarantees the availability of water in the root zone during water deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Applied as foliar treatment, such siliceous natural nanomaterials (SNNMs), have plant biostimulant effects, due to a combination of protection against UV radiation, an anti-transpirant effect and stimulation of photosynthesis [3]. Stimulation of photosynthesis results mainly from the local concentration effect of the siliceous natural nanomaterials on the CO2 [4]. Combinations of NPK foliar fertilizer and diatomaceous earth, and, respectively, zeolites, were tested for their influence on sweet almond (Prunus dulci) photosynthesis.…”
mentioning
confidence: 99%